2000
DOI: 10.1152/ajprenal.2000.278.1.f122
|View full text |Cite
|
Sign up to set email alerts
|

Age-related progressive renal fibrosis in rats and its prevention with ACE inhibitors and taurine

Abstract: Our previous studies demonstrated an increased reactive oxygen species (ROS) production, as well as transforming growth factor-beta1 (TGF-beta1) expression in the rat kidney with aging. In the present study, we examined the effect of aging on extracellular matrix (ECM) accumulation and the effects of treatment with angiotensin-converting enzyme inhibitors (captopril and lisinopril) and taurine, an antioxidant amino acid. Age-related increases in types I and IV collagen and fibronectin mRNA expression were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 25 publications
(30 reference statements)
4
44
0
1
Order By: Relevance
“…Glomerulosclerosis and tubulointerstitial fibrosis in 4M and 12M DSS rats aging (17,23,37). Recent studies have shown that in addition to excessive synthesis of the ECM, the presence of amorphous ECM deposits in progressive renal disease are due to decreased activity of the ECM degradative pathway (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerulosclerosis and tubulointerstitial fibrosis in 4M and 12M DSS rats aging (17,23,37). Recent studies have shown that in addition to excessive synthesis of the ECM, the presence of amorphous ECM deposits in progressive renal disease are due to decreased activity of the ECM degradative pathway (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The aging kidney is characterized by a decrease in GFR and renal blood flow (11)(12)(13), decreased urine-concentrating ability (14), increased responsiveness to angiotensin II and endothelin (15)(16)(17), decreased production of vasodilatory prostaglandins and nitric oxide (18,19), increased oxidative stress (20,21), and increased glomerulosclerosis and tubulointerstitial fibrosis (22,23). Glomerulosclerosis and tubulointerstitial fibrosis are hallmarks of progressive renal disease from diverse etiologies, and these renal pathologies are frequently observed in kidneys from aging animals and humans (17,22,23). Most studies have concentrated on the mechanisms underlying age-related glomerular changes, whereas the agerelated changes in the tubulointerstitium have received far less attention.…”
mentioning
confidence: 99%
“…Therefore, renal transsulfuration is important for Hcy clearance; it is responsible for the removal of ϳ20% of Hcy from the blood circulation in rats (10), and 78% of L-Hcy (added to the culture) was metabolized through the transsulfuration in isolated rat kidney cortical tubules (29). Meanwhile, there is accumulating evidence that several antioxidant Cys metabolites, such as glutathione (GSH, a reduced form), taurine, and hydrogen sulfide (H 2 S), exert protective effects against renal ischemia-reperfusion injury (9,24,48,74) and the progression of renal fibrosis (14,36,47).…”
mentioning
confidence: 99%
“…One of the early events of the ECM remodeling process is the activation of matrix metalloproteinases (MMPs) (8,39). Among MMPs, elastinases and collagenases are particularly important of matrix degradation in fibrotic occlusive diseases including renal fibrosis (5,21).…”
mentioning
confidence: 99%